Teachers’ Perspectives on the Learning Management System (LMS) in Physics Subject: A Preliminary Study - Nauratun Nazhifah; Apit Fathurohman (Jurnal Ilmiah Pendidikan Fisika, 2023)
This paper aims to explore the teachers’ perspectives on the LMS in the physics learning process. The research was conducted using a descriptive quantitative method. A total of 31 science and physics teachers participated as the research sample which was determined by purposive sampling technique. Data collection was carried out using a mixed questionnaire consisting of 14 questions which were then distributed online using Google Form. Based on the findings, learning using the LMS offers many advantages, but the findings also show that there are deficiencies in terms of the internet network which has an impact on delays in incoming information to students. Then, the results of the analysis show that 100% of science and physics teachers need the application and development of LMS to make it easier for them to convey physics material so that it is more flexible, effective, and efficient. The LMS expected by the physics teacher contains features such as video conferencing, uploading files/tasks, discussion forms, quizzes, and absences, then the LMS is user-friendly, can be used without the internet, and manages grades automatically. Based on the results of data analysis, it can be concluded that teachers seek the development and implementation of LMS in physics learning.